Упростить выражение:\left( {\frac{2}{{{x^2} - 1}} + \frac{1}{{x + 1}}} \right)({x^2} - x)...

0 интересует 0 не интересует
44 просмотров

Упростить выражение:\left( {\frac{2}{{{x^2} - 1}} + \frac{1}{{x + 1}}} \right)({x^2} - x) - x


спросил от (12 баллов) в категории Математика
1 Ответ
0 интересует 0 не интересует
ответил от Супер специалист (25.2k баллов)

Решите задачу:

\left( {\frac{2}{{{x^2} - 1}} + \frac{1}{{x + 1}}} \right)({x^2} - x) - x=\left( {\frac{2}{{(x - 1)(x+1)}} + \frac{1}{{x + 1}}} \right)({x^2} - x) - x=\\ =\left( {\frac{2}{{(x-1)(x+1)}} + \frac{x-1}{{(x-1)(x + 1)}}} \right)({x^2} - x) - x = \frac{(x+1)\cdot x(x-1)}{(x-1)(x+1)}-x= \\ =x-x=0

...